Odpowiedzi

  • Użytkownik Zadane
2009-10-13T16:24:18+02:00
A) (x+1)² - 2x²=x²+2x+1-2x²=-x²+2x+1
b) -2(3x-1)²+18x²=-18x²+12x-1+18x²=12x-1
c) 3(2a+1)(2a-1)=12a²-3
d) (x+8)(x-8)-(x² - 8 )=x²-64-x²+8=-56
e) -(x-4)²+ (x+4)²=-x²+8x-16+x²+8x+16=16x
f) (3t-1)² +(3t+1)(3t-1) =9t²-6t+1+9t²-1=18t²-6t

:)
2009-10-13T16:26:43+02:00
A) (x+1)do pot.2 - 2x do pot.2 =x²+2x+1
b) -2(3x-1)do pot.2 +18x do pot.2 =-18x²+12x-1
c) 3(2a+1)(2a-1) =12a²-3
d) (x+8)(x-8)-(x do pot.2 - 8 ) =x²-64-x²+8=-56
e) -(x-4)do pot.2 + (x+4)do pot.2 =16x
f) (3t-1)do pot.2 +(3t+1)(3t-1) =9t²-6t+1+9t²-1=-6t
2009-10-13T16:32:21+02:00
Uprość wyrażenia :
a) (x+1)do pot.2 - 2x do pot.2= (x+1)(x+1)-2x do potegi drugiej=x kwadrat +x+xkwadrat+1-2xdo potegi 2=x - po skroceniu
b) -2(3x-1)do pot.2 +18x do pot.2=-6x+2 do potegi 2+18x do potegi 2=36xkwadrat+4+324xkwadrat=360x+4
c) 3(2a+1)(2a-1)=(6a+3)(2a-1)=12akwadrat-6a+6a-3=12a kwadrat-3
d) (x+8)(x-8)-(x kwadrat - 8 )=x kwadrat-64-x kwadrat+8=-56
e) -(x-4)kwadrat+ (x+4)kwadrat=-x kwadrat+8x-16+x kwadrat+8x+16=16x
f) (3t-1)kwadrat +(3t+1)(3t-1) =9t kwadrat-6t+1+9t kwadrat-1=18t kwadrat-6t